Business case analysis of hybrid systems consisting of battery storage and power-to-heat on the German energy market. (December 2020) - Draheim, Patrick; Schlachter, Uli; Wigger, Henning; Worschech, Alena; Brand, Urte; Diekmann, Theys; Schuldt, Frank; Hanke, Benedikt; von Maydell, Karsten; Vogt, Thomas
Abstract: Declining prices on frequency containment reserve (FCR) markets endanger the profitability of battery energy storage systems (BESS). BESS combined with power-to-heat units could improve the economics both by supplying higher power rates on FCR markets and by converting excessive power into heat. Two cases were investigated with a techno-economic model using primary operation and market data of 2018/2019. The system amortises after 12 years with a net present value of two million € operating on the FCR market. No improvement was realized by additional arbitrage trading. Taxes, levies and charges frameworks are crucial for the economic success of hybrid systems. Highlights: A hybrid battery and power-to-heat system has been economically investigated. This hybrid system amortises in 12 years on the German FCR market. Hybrid systems are more profitable than standalone batteries. Additional arbitrage trading does not increase the profitability of hybrid systems. Diffusion of sector integrating systems is limited by taxes, levies and charges.